The History of Offshore Aquaculture in the Gulf of Mexico - Laura Tiu; Edward Camp (EDIS)
Aquaculture is a growing industry in Florida, and there is particular interest in offshore marine aquaculture. While inland and coastal aquaculture (like for shellfish or ornamental fish) is managed by the Florida state agency Florida Department of Agriculture and Consumer Services (FDACS), offshore aquaculture also involves federal management agencies. However, there has been some confusion and disagreement about which federal agencies will manage and make decisions about offshore aquaculture in the United States. This document describes a recent history and current state of that discussion. This information is important for potential aquaculturists and other stakeholders to understand, and should also provide guidance to management and outreach agencies seeking to inform stakeholders about offshore aquaculture.